Utility of Ascitic Fluid Adenosine Deaminase Levels in the Diagnosis of Tuberculous Peritonitis in General Medical Practice - Ayako Kumabe; Shuji Hatakeyama; Naoki Kanda; Yu Yamamoto; Masami Matsumura (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Tuberculous peritonitis is difficult to diagnose due to its varying clinical features, in addition to the low yield on bacterial culture or polymerase chain reaction using ascitic fluid samples. This study aimed to investigate the sensitivity and specificity of elevated adenosine deaminase (ADA) levels as a diagnostic marker for tuberculous peritonitis. Methods. A retrospective cohort of 181 adult patients who underwent ascitic fluid ADA level examination at Jichi Medical University Hospital between January 2006 and December 2015 were included. We collected data regarding ascitic fluid analyses including ADA levels, bacteriology and cytology, final diagnosis (cause of ascites), basis of the diagnosis, duration to diagnosis, and disease outcome. Results. Among 181 patients, elevated ascitic ADA levels (≥40 IU/L) were observed in 15 patients (median, 87.2 IU/L; range, 44.0–176.1 IU/L); 8 patients had tuberculous peritonitis, 4 had lymphoma-related ascites, and 2,had peritoneal carcinomatosis with bacterial coinfection, and 1 had chlamydial pelvic inflammatory disease. Among 166 patients without ascitic ADA level elevation (median, 7.3 IU/L; range, <2.0–39.1 IU/L), none had tuberculosis, 4 had lymphoma-related ascites, 28 had cancer/mesothelioma-related ascites, and 134 had ascites due to other causes. In our cohort, elevated ascitic fluid ADA levels (≥40 IU/L) showed 100% sensitivity, 96.0% specificity, 53.3% positive predictive value (PPV), and 100% negative predictive value for the diagnosis of peritoneal tuberculosis. Conclusions. Ascitic fluid ADA levels ≥40 IU/L showed excellent sensitivity, despite a low PPV, for the diagnosis of tuberculous peritonitis. Lymphoma-related ascites is an important mimic of tuberculous peritonitis that can result in high ascitic fluid ADA levels with similar clinical manifestations.